Peptidomics approaches to the discovery and ACE inhibitory effect of casein peptides derived from fermented bovine milk by kefir grains - Wang, Bo; Xiao, Shan; Cai, Yanxue; Chen, Xuan; Wang, Jihui (Frontiers in Sustainable Food Systems, 2023)
Introduction Kefir grains with efficient proteolytic system is an excellent starter culture for the production of bioactive peptides and milk products. This study explores the casein peptides derived from fermented bovine milk by kefir grains using the peptidomics approaches. The angiotensin converting enzyme (ACE) inhibitory activity of these peptides were also investigated. Methods After fermentation, peptidomics based on the LC-MS/MS was used to investigate the dynamic profile and the structure specificity of generated peptides. The ACE inhibitory activity of peptides was determined by measuring the amount of hippuric acid (HA) by a spectrophotometer at 228 nm. Results The results indicated that the cell envelope proteinases (CEPs) were the PI-/PIII-type. A total of 122 peptides were identified. The β-casein was preferentially hydrolyzed by kefir grains, and the main hydrolysis regions were f57-93, f132-160 and f192-209. The αs1-, and κ-casein were also hydrolyzed by a weaker degree. In the process of fermentation, the accumulated peptides increased with the fermentation time. The fermentation products exhibited ACE inhibitory activity, and this bioactivity remained 63% after simulated gastrointestinal (GI) digestion in vitro. Additionally, 14 Pro-containing peptides with ACE inhibitory activity were also identified. Conclusion These results provide new insights and evidence to investigate the bioactive milk peptides generated by kefir grains fermentation, as well as a reference for the development of functional foods.